VARIABEL LATEN SEBAGAI MODERATOR DAN MEDIATOR DALAM HUBUNGAN KAUSAL - ANTARA, I KOMANG GEDE; KENCANA, I PUTU EKA NILA; JAYANEGARA, KETUT (E-Jurnal Matematika, 2013)
Latent variables are variables that can not be measured directly. In analysis o f causal relationship involving three latent variables, one latent variable can be a moderator or mediator variables. Goodness of Fit moderation and mediation model of latent variables is affected by the value of the canonical correlation between moderator/mediator latent variables with the independent latent variables and dependent latent variables. If the value of both canonical correlation is well , so the Goodness of Fit models of mediation is getting better, while the opposite Goodness of Fit models will be better moderation .
Keywords: Latent Variables; Moderator; Mediator; Canonical Correlation